Case Report: A case of cytomegalovirus-related hemorrhagic cystitis early after pediatric kidney transplantation - Li, Jianming; Wu, Chenglin; Wei, Mengxun; Chen, Peisong; Su, Xiaojun; Hong, Mengzhi; Fu, Qian; Li, Jun; Liu, Longshan; Wang, Changxi (Frontiers in Pediatrics, 2025)
Cytomegalovirus (CMV) infections are commonly observed in immunocompromised patients. However, hemorrhagic cystitis (HC) is an exceptionally rare manifestation. Here, we report a pediatric kidney transplant recipient who developed CMV-related HC, presenting with acute painful macrohematuria, bladder wall thickening, and graft hydronephrosis during the early posttransplant period.